A Comparative Evaluation of Numerical and Analytical Solutions to the Biadhesive Single-Lap Joint. (10th March 2014) - Özer, Halil; Öz, Özkan
Abstract : This paper attempts to address the detailed verification of Zhao's analytical solution including the moment effect with the two- and three-dimensional finite element results. Zhao compared the analytical results with only the 2D FEA results and used the constant bond-length ratio for the biadhesive bondline. In this study, overlap surfaces of the adherends and the adhesives were modelled using surface-to-surface contact elements. Both analytical and numerical analyses were performed using four different biadhesive bondline configurations. The 3D FEA results reveal the existence of complex stress state at the overlap ends. However, the general results show that analytical and numerical results were in a good agreement.